Response of photosynthetic apparatus of two Deschampsia species with different distribution areas on abiotic stress - Taran, N. Yu.; Storozhenko, V.; Okanenko, A.; Batsmanova, L. M.; Svietlova, N. B. (Ukrainian Antarctic Journal, 2013)
Deschampsia antarctica (endemic of Antarctic region) and Deschampsia caespitosa (inhabitant of moderate climate regions) are two plant species of Poaceae. The influences of UV-B radiation and H2O2 on photosynthetic apparatus of these plants were studied. UV-B radiation induced degradation of chlorophyll a and β-carotene in leaves of plants of both Deschampsia species. The content of galactolipids in leaves of both species under conditions of UV-B radiation varied significantly, but comparatively stable sulfoquinovosyldiacylglycerol (SQDG) content was observed. UV-B radiation caused slight decrease of QA pool oxidation level in D. antarctica leaves and increase of this index in leaves of D. caespitosa plants. Also UV-B action induced slight decrease of non-photochemical quenching in D. caespitosa leaves, but PS II quantum efficiency of charge separation φp was unchanged. The ratio between the monomeric and oligomeric forms of LHC II (LHCP1/LHCP3) in photosynthetic apparatus of leaves of irradiated plants increased, especially significantly in leaves of D. caespitosa plants. H2O2 treatment cause insignificant decrease of SOD activity of both species. Pigment composition was characterized by increase of carotenoids content in leaves of D.antarctica plants and chlorophyll a content in both species. Glycolipid content was stable and SQDG content slightly increased in leaves of D.antarctica plants after H2O2 treatment.